Energy absorption characteristics of butterfly-shaped multi-cellular honeycomb structures under compressive loading - Yifeng, Zhong; Rong, Liu; Hien, Poh Leong; Xiaoquan, Liu; Yuxin, Tang (Structures (Oxford), 2025)
Replacing the inclined struts in re-entrant honeycombs with butterfly-shaped curved struts is intended to enhance both stiffness and energy absorption. To reduce modeling complexity, a three-dimensional equivalent Cauchy model (3D-ECM) for butterfly-shaped multi-cellular honeycomb structures (butterfly MHS) was developed within the framework of variational asymptotic method. The 3D-ECM’s accuracy in predicting elastic compressive behavior was validated against 3D finite element model results and compression tests on 3D-printed specimens, with maximum errors within 8.67% for displacement, strain energy, and local field distribution. Strain energy analysis revealed that the normal strain energy (SE22) primarily contributes to transverse contraction, while the high shear strain energy along the 1–2 plane (SE12) indicates notable auxetic deformation. Energy–displacement curve analysis indicated that butterfly MHS exhibits the highest strain energy, demonstrating strong energy absorption capacity. Parameter studies revealed that increasing the arc radius and cell height enhances the auxetic effect, improving elastic compressive behavior. Importantly, the 3D-ECM reduced number of elements and model complexity, improving computational efficiency without loss of accuracy. Notably, the butterfly MHS outperformed both re-entrant and hexagonal MHS in elastic compressive behavior and specific energy absorption by 32% with identical dimensions and materials, significantly expanding its potential applications in construction engineering requiring lightweight and high-strength materials.